Photoacoustic technique for noninvasive glucose sensing : principles and implementations - Zhang, Ruochong (Nanyang Technological University, 2020)
Diabetes Mellitus is a kind of chronical metabolic disorder that cannot be completely cured. It is caused by lack of insulin or insulin resistance and characterized by abnormally high blood glucose levels. It can lead to complications including cardiovascular disease, kidney disorder, eye damage and even result in death, if not properly treated. Hence, tight control of blood glucose level is crucial for diabetic patients. However, the commercially available glucose meters used for homecare are mainly invasive and based on glucose oxidase which is also costly. Although, several noninvasive devices are under development using fluorescent, ultrasonic, thermal and electromagnetic methods, none of them has passed the market test yet. It is still worth exploiting truly noninvasive glucose monitoring technique for clinical application. Plenty of attempts had been devoted to noninvasive glucose monitoring employing different techniques. Most of them are optical methods with a few other exceptions using bio-impedance spectroscopy, and electromagnetic sensing. Among those traditional optical methods, major problems lie in sensitivity, specificity and penetration depth. Photoacoustic (PA) technique, on the other hand, compensates the diffusion and diffraction limits faced by pure optical methods by detecting the acoustic signal, induced by the tissue absorption and thermal expansion, since acoustic wave suffers ~10^3 less scattering than light. Meanwhile, the excellent contrast of optics is maintained in PA. This PhD thesis comprehensively investigates the fundamental physics behind photoacoustic phenomenon and combines the findings with glucose detection to realize the specific biomedical application. Furthermore, a fully integrated portable photoacoustic sensor was designed, developed and tested for noninvasive glucose sensing. In the introduction, background and urgent need of the noninvasive glucose monitoring device were described which are the motivations of this thesis. Then, several state-of-the-art noninvasive glucose monitoring techniques are comprehensively introduced and compared to show the advantage of photoacoustics in Chapter 2, followed by the detailed discussion about working principal and relationship between biological components and photoacoustic signal generation. In Chapter 3 to 5, novel findings and methods including accuracy enhancement by data fusion, sensitivity improvement by indirect photoacoustic method, multidimensional waveform analysis and their corresponding performance on noninvasive glucose measurement are presented. Next, a study on system design and development for noninvasive glucose measurement is conducted in Chapter 6, targeting for real clinic and homecare application. The final goal is to commercialize the research achievement and replace the current finger-prick glucose meters to improve the quality of diabetic management. In the last chapter, a conclusion is drawn and some future work is recommended. In summary, this thesis comprehensively investigates photoacoustic effect and utilizes the novel findings on the application for noninvasive glucose sensing, which can be regarded as translational research. Interesting concepts are proposed and experiments on glucose in the physiological range are demonstrated. Implementation of developing a portable photoacoustic sensor is also carried out, which could be the potential replacement of the invasive devices in the market now.